Global burden of childhood otitis media attributable to secondhand smoke from 1990 to 2021: a systematic analysis of the global burden of disease study 2021 - Li, Bei; Pan, Qingchun; Zou, Kai (Frontiers in Pediatrics, 2025)
BackgroundChildhood otitis media is significantly influenced by exposure to secondhand smoke (SHS), posing a considerable challenge to pediatric health. Utilizing data obtained from the Global Burden of Disease Study (GBD) 2021, this population-based burden analysis examines the worldwide impact of SHS-associated otitis media among children aged 0–14 years between 1990 and 2021, while forecasting epidemiological patterns up to 2051.MethodsThe GBD 2021 dataset served as the foundation for evaluating four key metrics: disability-adjusted life years (DALYs), age-standardized rates for DALYs (ASDR), years lived with disability (YLDs), and age-standardized YLD rates (ASYR) associated with pediatric middle ear infections caused by SHS exposure. Joinpoint regression modeling was employed to detect epidemiological trend change points, while disparity assessment in health outcomes examined variations across socioeconomic and demographic strata. Burden projection was conducted through implementation of an autoregressive integrated moving average (ARIMA) statistical framework.ResultsThe global YLDs due to childhood otitis media attributable to SHS decreased by 17.65% in 1990–2021. The ASYR decreased by 28.78%, from 5.49 [95% uncertainty interval (UI): 2.38–9.9] per 100,000 to 3.91 (95% UI: 1.66–7.23) per 100,000. The ASDR falling by 32.08%, from 5.83 (95% UI: 2.61–10.37) per 100,000 to 3.96 (95% UI: 1.68–7.31) per 100,000. The burden was consistently greater in males compared to females, with the highest impact observed in regions with low and middle SDI regions. Joinpoint regression analysis revealed the greatest decline in ASYR occurred in 2003–2008, while the most significant decrease in ASDR occurred in 1994–1999. Health inequality analysis showed a reduction in inequality from 1990 to 2021. ARIMA projections suggest a further decline in global ASYR and ASDR by 2051, although an increase may occur in middle SDI regions.ConclusionWhile there has been a general decrease in the global burden of childhood otitis media linked to secondhand smoke exposure. Certain regions (notably Central Asia, North Africa/Middle East, and Oceania) continue to experience a disproportionately high burden. These findings call for continued investment in public health strategies that not only limit SHS exposure but also address healthcare access gaps in underserved populations.